Developing a Deductive Training Model for Tour Guides in Goa Pindul to Promote Inclusive Tourism - Prasetyo, Iis; Dewi, Adin Ariyanti; Tohani, Entoh; Rofiq, Akhmad (Universitas Negeri Padang, 2025)
The purpose of this study is to investigate the feasibility of developing a deductive training model for tour guides in Pindul Cave. ADDIE is the research approach used during the development, implementation, and assessment stages. Data were obtained through Focus Group Discussion (FGD) and then examined quantitatively by comparing the FGD results to the results of the implemented training. The research results showed that 1) deductive training materials were developed using two main approaches, namely inclusive tourism theory and practical simulation, 2) training implementation was applied to 20 tour guides for two days, with the result that 85% of the guides were able to apply inclusive scouting skills effectively, and 3) training evaluation was carried out using tests and was also carried out directly, with the results that the guide's knowledge increased.